Towards Evidence-Based Legitimacy Interventions in EU Law: Challenges and Directions for Empirical Research - Eva Grosfeld; Armin Cuyvers; Daan Scheepers (Utrecht Law Review, 2023)
As EU institutions are increasingly being asked to address societal challenges, the legitimacy need of the EU becomes more evident. With the aim of complementing the already rich literature on normative EU legitimacy and ultimately enabling evidence-based legitimation strategies, this contribution identifies and addresses gaps in empirical research on perceived EU legitimacy, which pertain to conceptualization, operationalization and explanatory factors. To that end, we first of all define perceived EU legitimacy as the perception among EU citizens that the EU’s exercise of authority is appropriate. Drawing on the relational approach to legitimacy, these perceptions arise from socially held norms about how the EU should rightfully exercise authority, which are in turn influenced by the socio-political context. We then propose ways in which such a conception of legitimacy can be operationalized in empirical research. Finally, we lay the foundation for a theoretical model on the sources of EU legitimacy perceptions, arguing that such a model should consider social psychological processes related to identity and morality, because these factors influence how people process information about the EU, and are increasingly part of the environment in which norms about rightful rule arise. Once empirical research is better equipped to understand these processes underlying citizens’ legitimacy perceptions of the EU, opportunities arise to develop evidence-based interventions and inform legal practices in the EU with extra-legal insights. As EU legitimation through policies, legal reform and institutional design requires knowledge of legal feasibility, social scientists and lawyers should collaborate to embed empirical insights in EU law. Bridging the norm-fact divide in this manner is both normatively desirable and empirically necessary for the EU to strengthen its legitimacy and face societal challenges.